The EAACI/GA2LEN/EDF/WAO Guideline for the definition, classification, diagnosis, and management of urticaria: the 2013 revision and update. Issue 7 (30th April 2014) - Zuberbier, T.; Aberer, W.; Asero, R.; Bindslev‐Jensen, C.; Brzoza, Z.; Canonica, G. W.; Church, M. K.; Ensina, L. F.; Giménez‐Arnau, A.; Godse, K.; Gonçalo, M.; Grattan, C.; et al.
Abstract This guideline is the result of a systematic literature review using the 'Grading of Recommendations Assessment, Development and Evaluation' (GRADE) methodology and a structured consensus conference held on 28 and 29 November 2012, in Berlin. It is a joint initiative of the Dermatology Section of the European Academy of Allergy and Clinical Immunology (EAACI), the EU‐funded network of excellence, the Global Allergy and Asthma European Network (GA2LEN), the European Dermatology Forum (EDF), and the World Allergy Organization (WAO) with the participation of delegates of 21 national and international societies. Urticaria is a frequent, mast cell‐driven disease, presenting with wheals, angioedema, or both. The life‐time prevalence for acute urticaria is approximately 20%. Chronic spontaneous urticaria and other chronic forms of urticaria do not only cause a decrease in quality of life, but also affect performance at work and school and, as such, are members of the group of severe allergic diseases. This guideline covers the definition and classification of urticaria, taking into account the recent progress in identifying its causes, eliciting factors and pathomechanisms. In addition, it outlines evidence‐based diagnostic and therapeutic approaches for the different subtypes of urticaria. This guideline was acknowledged and accepted by the European Union of Medical Specialists (UEMS).